2012
DOI: 10.1186/1687-1499-2012-116
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CACC string stability using SUMO, Simulink, and OMNeT++

Abstract: Recent development in wireless technology enables communication between vehicles. The concept of cooperative adaptive cruise control (CACC)-which uses wireless communication between vehicles-aims at string stable behavior in a platoon of vehicles. "String stability" means any non-zero position, speed, and acceleration errors of an individual vehicle in a string do not amplify when they propagate upstream. In this article, we will discuss the string stability of CACC and evaluate its performance under varying p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…In [9], for instance, it was found that the ratio of correctly received packets drops to values below 10% on a motorway junction with high traffic density, assuming all vehicles are equipped with wireless communication devices. Taking packet loss into account, [10] focused on H ∞ controller synthesis, whereas the experimental study described in [11] analyzed the effects on string stability for a given controller.…”
mentioning
confidence: 99%
“…In [9], for instance, it was found that the ratio of correctly received packets drops to values below 10% on a motorway junction with high traffic density, assuming all vehicles are equipped with wireless communication devices. Taking packet loss into account, [10] focused on H ∞ controller synthesis, whereas the experimental study described in [11] analyzed the effects on string stability for a given controller.…”
mentioning
confidence: 99%
“…Some limitations and uncertainties in practical vehicular networking, such as transmission range, packet loss, and probabilistic transmission delay, may have negative impacts on the platoon control system performance [66]. Consequently, it is critical to clarify how these communication constraints and uncertainties affect the platooning system and how to implement the vehicle platooning under such communication uncertainties.…”
Section: Cooperative Platoon Drivingmentioning
confidence: 99%
“…Lei et al [66] investigated the platoon stability of a CACC system in the presence of imperfect communication. They conducted the simulation by coupling traffic simulator with networking simulator.…”
Section: A Modeling Platoon-based Vcpssmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Omae et al (4) have reported a CACC design for trucks, along with an accompanying simulation-based evaluation, while Xu and Raja (5) have analyzed the difference in behavior of ACC and CACC with regard to lane merging. Finally, Lei et al (6) have evaluated the influence of V2V communication packet loss on control.…”
Section: Related Workmentioning
confidence: 99%